1991
DOI: 10.1002/bip.360311202
|View full text |Cite
|
Sign up to set email alerts
|

Unfolding of an α‐helix in water

Abstract: We describe a 1 ns molecular dynamics simulation of an 18-residue peptide (corresponding to a portion of the H helix of myoglobin) in water. The initial helical conformation progressively frays to a more disordered structure, with the loss of internal secondary structure generally proceeding from the C-terminus toward the N-terminus. Although a variety of mechanisms are involved in the breaking of helical hydrogen bonds, the formation of transient turn structures, with i----i + 3 hydrogen bonds, and bifurcated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

21
123
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 143 publications
(144 citation statements)
references
References 41 publications
21
123
0
Order By: Relevance
“…Following the Zimm-Bragg theory of the helix-coil equilibrium (7), it has been established that short polypeptides should not form helices in water. Indeed, numerous studies report that the relative tendency for helix formation in water is low at physiological temperatures (6,8).The structure of polyalanine peptides is of considerable interest as, in general, regardless of specific chemical environments, the commonly reported secondary structure propensity scales for amino acids (9-11) rank alanine as having the highest ␣-helical propensity. However, experimental (12-14) and computational (4-6, 15-23) studies showed that polyalanines tend to adopt random-coil conformations in aqueous solution.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Following the Zimm-Bragg theory of the helix-coil equilibrium (7), it has been established that short polypeptides should not form helices in water. Indeed, numerous studies report that the relative tendency for helix formation in water is low at physiological temperatures (6,8).The structure of polyalanine peptides is of considerable interest as, in general, regardless of specific chemical environments, the commonly reported secondary structure propensity scales for amino acids (9-11) rank alanine as having the highest ␣-helical propensity. However, experimental (12-14) and computational (4-6, 15-23) studies showed that polyalanines tend to adopt random-coil conformations in aqueous solution.…”
mentioning
confidence: 99%
“…These interactions involve the effect of organic solvents on the destabilization of the hydrophobic core and the exposure of side chains, as well as the opposite effects of aqueous solvents on the protein structures favoring the hydrophilic protein surface and the hydrophobic core (1,3). Theoretical and computational evidence (4)(5)(6) for medium effects on polypeptide structures has accumulated. Following the Zimm-Bragg theory of the helix-coil equilibrium (7), it has been established that short polypeptides should not form helices in water.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of computer simulations have addressed the (~/3~,,/ coil equilibrium, both in AIB-rich peptides (Smythe et al, 1993;Basu et al, 1994;Huston & Marshall, 1994;Zhang & Hermans, 1994), and in proteins and peptides with no AIB residues (Soman et al, 1991;Tirado-Rives & Jorgensen, 1991;Tirado-Rives et al, 1993). Some of these studies suggest that the 3,,,-helix is a kinetic intermediate along the a-helix unfolding pathway (Soman et al, 1991;Tirado-Rives & Jorgensen, 1991;Tobias & Brooks, 1991).…”
mentioning
confidence: 99%
“…Some of these studies suggest that the 3,,,-helix is a kinetic intermediate along the a-helix unfolding pathway (Soman et al, 1991;Tirado-Rives & Jorgensen, 1991;Tobias & Brooks, 1991). 310-Helices have also been proposed as thermodynamic intermediates where helical peptides of moderate stability exist as a mixture of a-and 310-structures (Millhauser, 1995;Sheinerman & Brooks, 1995).…”
mentioning
confidence: 99%